EKSTRAKURIKULER PRAMUKA DALAM MEMBENTUK KARAKTER KERJA SAMA DAN KEMANDIRIAN SISWA SEKOLAH DASAR - Hidayati, Romi; Ruli Astuti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Schools as formal educational institutions have a significant role in shaping students’ character.One of the efforts to shape the character of students is to participate in scouting extracurricularactivities. This study aims to examine the implementation of scouting extracurricular activitiesin shaping students’ character, particularly in terms of teamwork and self-reliance.This studyaims to analyze the implementation of scouting extracurricular activities in developingstudents' cooperation and independence, as well as to examine the supporting and inhibitingfactors. This research uses a qualitative approach with a case study method. The study wasconducted at SDN Japanan 3, Gempol District, Pasuruan Regency. Data collection techniques inthis research include observation, interviews, and documentation. The results show thatscouting activities at SDN Japanan 3 are carried out in a structured manner with the support ofcompetent scoutmasters to train students in developing cooperation and independence. Theseactivities include skills such as setting up tents, making stretchers, marching, and knottingtechniques. The main inhibiting factor in the implementation of scouting activities at SDNJapanan 3 is the school does not have scout lodge.